A Divided City in a Time of Pandemic: Dispatches from Doha - Uday Chandra (14779261) (2020)
Doha, once a sleepy Indian Ocean port and now a symbol of Qatar’s rise as a petro-state, is a city divided between its wealthy citizens and resident aliens and the migrant workers that serve them. The city’s spatial divisions are rooted in its transoceanic history as much as its makeover as an urban experiment in authoritarian modernism (Hashim, Irazábal, and Byrum 2010). As Qatar’s monarchical regime liberalized its economy with an eye to the post-hydrocarbon future (Nonneman 2006), Doha came to be defined by imposing edifices towering over awestruck subjects and a lack of public spaces and street corners in which different strata of society can mingle or gather freely. With the arrival of COVID-19, the well-planned residential neighborhoods of wealthy citizens and expatriates seem starkly separated from those of the working poor even as their dependence on each other is arguably greater than ever before. This deeply divided city, wrestling with the politics of contagion, shows how logics of exclusion and interdependence are, paradoxically, intertwined inextricably. Other Information Published in: City & Society License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/ciso.12310